New method of temperature and conductivity sensor calibration with improved efficiency for screening SBE41 CTD on Argo floats - Shigeki Hosoda; Mizue Hirano; Takayuki Hashimukai; Satoko Asai; Noriko Kawakami (Progress in Earth and Planetary Science, 2019)
Abstract The global ocean monitoring system would benefit from improvements in the efficiency of Conductivity, Temperature, and Depth Device (CTD) sensor screening. Here, we describe the development of a new screening system, J-Calibration, for use with the SBE41 CTD sensor on the Argo float (Sea Bird Scientific). This new system has crucial advantages over the traditional SBE-Calibration system. First, J-Calibration does not require removal of the CTD sensor unit from the Argo float body to operate in a laboratory. This feature enables technicians or operators to more efficiently check the Argo target accuracies (± 0.005 °C for temperature and ± 0.01 PSS-78 for salinity) and allows the manufacturer’s warranty to remain intact. This also allows for a more efficient basic screening system which maintains screening accuracy without the need for specialized technicians. J-Calibration reduces the screening time to 1/6th that of SBE-Calibration and does not require the preparation of large amounts of artificial seawater. J-Calibration uses 1/23rd of the volume of seawater compared to SBE-Calibration by examining calibration at only 1 temperature point (22 °C), whereas SBE-Calibration requires 7 points to achieve calibration. The J-Calibration system does require careful temperature control of the artificial seawater as it is critical to maintain a uniform water temperature throughout the experiments. To satisfy this, using a vinyl greenhouse and covering sensors with adiabatic materials and cooling packs are effective. In comparison with the accuracy and system stability of SBE-Calibration, we show that the J-Calibration system is non-inferior and therefore is suitable for use in laboratory screening prior to deployment. Based on these advantages, the J-Calibration system will make a strong contribution to the deployment of healthy Argo fleets and to the maintenance of uniform data in the global ocean.